Pelatihan Pembuatan Pupuk Organik Padat Berbahan Dasar Kotoran Sapi di Desa Sukowono - Faizal Rizki; Ulfa Maunatul Khasanah; Chusnul Khotimah; Monica Yulia; Fadhila Syaqwa Ahqmara; Kiko Irianto; Adelia Putri Anggre Aini; Ajung Gilang Putra Raharja; Malika Hasanah; Erika Ersa Della; Laily Mutmainnah (Penerbit Goodwood, 2026)
Purpose: The aim of this program is to increase knowledge, skills and encourage farmers' independence in managing solid cow dung waste into solid organic fertilizer so that they do not depend on subsidized fertilizer. Methodology: Community service activities are carried out through training for farmer groups in Sukowono Village. The first stage is the formulation and discussion of the problem, followed by training in making organic fertilizer from cow dung. After making fertilizer, a regular monitoring process is carried out to ensure decomposition is going well. The final stage is evaluation to determine the success of making fertilizer. Results: Based on the discussions that had been carried out, problems were found regarding piles of cow dung waste. so the solution is to make solid organic fertilizer. The implementation stage is carried out by socializing the program, making manure, and monitoring fertilizer. Based on indicators, the organic fertilizer made shows success. Conclusions: Utilization of cow dung waste as solid organic fertilizer provides an effective solution to overcome environmental pollution and increase agricultural productivity. Limitations: Solid organic fertilizer is produced from processed cow dung and can be used to improve soil fertility and support plant growth. Contributions: This community service activity contributes to the transfer of knowledge to farmers in the surrounding area. In addition, community service activities contribute to introducing Jember University to the community and highlighting the role of science in improving farmers' knowledge and skills.